Visitors get a taste of Felda life - Sunday, Star (Sunday Star, 2014)
THE residents of Felda Chini 1, Pekan, Pahang recently became foster families to 40 students from Universiti Utara Malaysia's (UUM) Proton Students' Residential Hall. The three-day programme saw the students taking part in a wide range of activities such as communal cleaning (gotong-royong), cooking roti jala, fishing and even feeding goats.